Fabrication of Silk Microstructures Using Photolithography. Issue 1718 (2015) - Pal, Ramendra K.; Kurland, Nicholas E.; Kundu, Subhas C.; Yadavalli, Vamsi K.
ABSTRACT: Precise spatial patterns and micro and nanostructures of peptides and proteins have widespread applications in tissue engineering, bioelectronics, photonics, and therapeutics. Optical lithography using proteins provides a route to directly fabricate intricate, bio-friendly architectures rapidly and across a range of length scales. The unique mechanical strength, optical properties, biocompatibility and controllable degradation of biomaterials from silkworms offer several advantages in this paradigm. Here, we present the biochemical synthesis and applications of a "protein photoresist" synthesized from the silk proteins, fibroin and sericin. Using light-activated direct-write processes such as photolithography, we show how silk proteins can form high resolution, high fidelity structures in two and three dimensions. Protein features can be precisely patterned at sub-microscale resolution (µm) at the bench-top over macroscale areas (cm), easily and repeatedly with high-throughput. For instance, periodic, microstructured arrays can be patterned over large areas to form structurally induced iridescent patterns and functional opto-electronic structures. We further demonstrate how photocrosslinked protein micro-architectures can function for the spatial guidance of cells without use of cell-adhesive ligands as biocompatible and biodegradable scaffolds. The ease of biochemical functionalization, biocompatibility, as well as favorable mechanical properties and biodegradation of this silk biomaterial provide opportunities for otherwise inaccessible applications as sustainable, bioresorbable protein microdevices.